Ménière's Syndrome or Disease. Issue 8 (September 2015) - Syed, Mohammed Iqbal; Ilan, Ophir; Leong, Annabelle C.; Pothier, David D.; Rutka, John A.
<x xml:space="preserve">Abstract</x> Objective To evaluate the evidence and trends in published literature on the treatment of Ménière's syndrome or disease (MS/D) by comparing studies published in the last two decades. Data Sources A literature search was performed on AMED, EMBASE, HMIC, MEDLINE, PsycINFO, BNI, CINAHL, HEALTH BUSINESS ELITE, CENTRAL and Cochrane Ear, Nose and Throat disorders groups trials register using a combination of MeSH. The date of last search was October 2014. Study Selection and Data Extraction Two hundred five studies (104 in decade I and 101 in decade II) were evaluated to report trends in the management of this condition, the differing levels of evidence published for each treatment modality, evaluate whether the guidelines published by the AAOHNS-Committee on Hearing and Equilibrium had been correctly employed, and whether the randomized controlled trials (RCTs) were compliant with the CONSORT guidelines. Results The number of published RCTs almost tripled from decade I (1994–2003) to decade II (2004–2103). There was a significant decline in the use of surgical intervention (p = 0.013); however, the number of studies involving the use of intratympanic injection remained largely unchanged. There was a shift in the level of evidence in published studies; studies with level 1 evidence tripled from decade I to II (4.8 to 17.8%, respectively) (p = 0.03); however, compliance with the AAOHNS-CHE criteria for reporting treatment outcomes and the CONSORT checklist was still poor. Conclusion Although the evidence base on published literature on MS/D has improved over the last decade with an increase in emphasis on RCTs and quality of life (QoL) studies, a significant number of studies failed to follow AAOHNS-CHE criteria for reporting treatment outcome and the CONSORT criteria for reporting RCTs.